Analisis Gelombang Elektromagnetik dan Seismik yang Ditimbulkan oleh Gejala Gempa - Andre, Hanalde; Hazmi, Ariadi; Timor, Agus Rahmad (JURNAL NASIONAL TEKNIK ELEKTRO, 2016)
Earthquakes are a natural phenomenon which is difficult to predict when and how it will happen. Effort is needed to minimize the risk of earthquakes, such as the observation of the early signs before an earthquake occurs (precursor). This study was conducted to observe earthquakes in West Sumatra in two ways. Observations eleketromagnetik waves utilizing radio waves from the two stations. The study also uses seismic wave sensors that are placed in the Department of Electrical Engineering, University of Andalas. Based on the results of data processing of the transmission of radio waves, it is known that electromagnetic anomalies can be recorded by utilizing radio wave propagation. However, with the line of sight propagation cause a lot of loss propagation, and less effective in recording. For the recording of the earthquake through the seismic waves very well. The measurement results for the direction of the epicenter compared with the measurement result BMKG for some earthquakes end of 2013 were felt in the West Sumatra. The average error of measurement gained 9.6% since the phase delay is affected by the accuracy of the sensor device.Keywords: Earthquakes, Electromagnetic, SeismicAbstrak- Gempa bumi adalah fenomena alam yang sulit diprediksi kapan dan bagaimana akan terjadi. Diperlukan usaha untuk meminimalisir resiko gempa bumi, seperti pengamatan tanda tanda awal sebelum gempabumi terjadi (prekursor). Penelitian ini dilakukan untuk mengamati kejadian gempa di Sumatera Barat melalui dua cara.Â  Pengamatan gelombang eleketromagnetik memanfaatkan gelombang radio dari dua stasiun. Penelitian juga menggunakan sensor gelombang seismic yang ditempatkan di jurusan Teknik Elektro, Universitas Andalas. Berdasar hasil pengolahan data dari transmisi gelombang radio, maka diketahui bahwa anomaly elektromagnetikÂ  dapat direkam dengan memanfaatkan propagasi gelombang radio. Namun propagasi dengan line of sight banyak menimbulkan rugi-rugi propagasi, dan kurang efektif dalam perekaman. Untuk rekaman gempa melalui gelombang seismik sangat baik. Hasil pengukuran untuk arah pusat gempa dibandingkan dengan hasil pengukuran BMKG untuk beberapa kejadian gempa akhir tahun 2013 yang dirasakan di Sumatera Barat. Adapun error rata-rata pengukuran yang didapat 9.6% karena dipengaruhi oleh keakurasian delay phasa alat sensor.Kata kunci: Gempa bumi, Elektromagnetik, Seismik